Entrepreneurship Education in Higher Education of Selected Countries - Hamid Rahimi (Comparative Education Society of Iran ( CESIR), 2021)
Due to the vital role of entrepreneurship, many efforts have been made to improve and promote it, the most important of which is the provision of entrepreneurship education programs in universities and educational institutions in different countries of the world. By studying the experiences of other countries, a proposed model for entrepreneurship education in Iran can be reached. The purpose of this research was to study of entrepreneurship education in higher education in selected countries comparatively. The research questions edited to considering types entrepreneurship education in terms of location, structure and trainers of entrepreneurship education. The method of the present study was a qualitative adaptation based on the use of a four-stage Bereday’s approach. The statistical population included different countries of the world and statistical sample consisted of several countries such as United States, Germany, Netherland, Philippine & Australia that were selected through purposive sampling. The method of data collection was documented and the validity of documents was assessed through internal evaluation (content accuracy) and external evaluation (document accuracy). Qualitative content analysis method was used to analyze the data. The findings showed that entrepreneurship education in all five countries studied is done more in the educational environment than in the workplace. In terms of types of educators (field specialists, entrepreneurship specialists and in combination), the highest similarity was between the United States, Philippine and Germany, and the Netherland and Australia were different from the other three countries. In terms of structure (single course, course and certification), the similarities were more in the form of single course and course. According to the findings, the appropriate model of entrepreneurship education in higher education in Iran can be used as a model for compiling courses (in the form of discipline, orientation, interdisciplinary and integrated) in all educational fields (Humanities, Engineering, Basic Sciences, Art and Medicine) or be formulated as an entrepreneurial university.